Role of gC1qR as a modulator of endothelial cell permeability and contributor to post-stroke inflammation and edema formation - Delgardo, Mychael; Tang, Anthony J.; Tudor, Thilan; Pascual-Leone, Andrés; Connolly, E. Sander (Frontiers in Cellular Neuroscience, 2023)
Ischemic stroke is a leading cause of death and disability worldwide. A serious risk of acute ischemic stroke (AIS) arises after the stroke event, due to inflammation and edema formation. Inflammation and edema in the brain are mediated by bradykinin, the formation of which is dependent upon a multi-ligand receptor protein called gC1qR. There are currently no preventive treatments for the secondary damage of AIS produced by inflammation and edema. This review aims to summarize recent research regarding the role of gC1qR in bradykinin formation, its role in inflammation and edema following ischemic injury, and potential therapeutic approaches to preventing post-stroke inflammation and edema formation.